2016
DOI: 10.1097/md.0000000000002862
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Transverse Sinus Hypoplasia in Magnetic Resonance Venography

Abstract: In previous studies of transverse sinus (TS) hypoplasia, discrepancies between TS diameter measured by magnetic resonance venography (MRV) and contrast T1-weighted magnetic resonance (contrast T1) were observed. To investigate these discrepancies, and considering that TS hypoplasia is associated with neurological disorders, we performed a post hoc analysis of prospectively collected data from 3 case–control studies on transient global amnesia (TGA), transient monocular blindness (TMB), and panic disorders whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The right transverse sinus is usually larger than the left and asymmetry of the transverse sinuses is not uncommon [ 12 ]. Unilateral hypoplasia or aplasia, which was also found in the present study, can be observed in 20% to 39% of cases [ 12 - 14 ]. In this study, the mean diameter of the transverse sinus was 6.21 mm and 6.30 mm on right and left sides, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The right transverse sinus is usually larger than the left and asymmetry of the transverse sinuses is not uncommon [ 12 ]. Unilateral hypoplasia or aplasia, which was also found in the present study, can be observed in 20% to 39% of cases [ 12 - 14 ]. In this study, the mean diameter of the transverse sinus was 6.21 mm and 6.30 mm on right and left sides, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The detailed distribution of subjects with and without TS hypoplasia was reported in Table 1 of our previous paper [10]. In summary, 38% (17), 33% (8), 43% (9) and 68% (28) of the subjects with TGA, TMB, panic disorder, and controls, respectively, are with no TS hypoplasia.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, asymmetry of the TS was successfully measured using magnetic resonance venography (MRV) and contrast T1-weighted magnetic resonance imaging (contrast T1) in transient global amnesia (TGA) and transient monocular blindness (TMB) [ 8 , 9 ]. Furthermore, two types of TS hypoplasia (anatomical TS hypoplasia and flow-related TS hypoplasia) were recently distinguished using a post-hoc analysis of the discrepancy and conformance of TS diameters measured by MRV and contrast T1 [ 10 ]. While anatomical TS hypoplasia is associated with TS diameter conformance, flow-related TS hypoplasia only appears on MRV due to downstream internal jugular vein (IJV) or brachiocephalic vein (BCV) compression/stenosis, and has been associated with neurological disorders of venous outflow impairment [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even neurological disorders that used to be assumed to have nothing to do with the vasculature, including multiple sclerosis and normal pressure hydrocephalus, now have been shown to involve venous hemodynamic mechanisms (Beggs, 2013). Interestingly, special MR sequence revealed that some neurological disorders, such as transient monocular blindness, panic disorder and transient global amnesia were correlated with transverse sinus hypoplasia (Han et al, 2016). Hence, it is now gradually being accepted that venous congestion and insufficiency not only affects the regional blood movement, but also the circulation of CSF, and overall brain metabolism and functional activity (Beard et al, 2015; Muir and Macrae, 2016).…”
Section: The Importance Of Identifying Cerebral Venous System Alteratmentioning
confidence: 99%